DEVELOPMENT OF AUDIOVISUAL LEARNING MEDIA BASED ON WORDWALL APPLICATIONS TO IMPROVE LITERACY SKILLS - Sakamurti, Novida Ari; Nugroho, Wahyu; Pratiwi, Diyanti Jati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Mataram, 2024)
In the world of education, teachers are required to play an important role in supporting students' learning. Efforts that can be made are using learning media. One of them is the use of audiovisual learning media to clarify the material so that learning objectives can be achieved. However, its use is often inappropriate, where in learning, student literacy is lacking and even student interest in knowledge is very low. Based on these problems, improving student literacy can be overcome using the online game learning media Wordwall. The aim of this research is to increase the literacy of fourth grade elementary school students. R&D research method the sampling technique used is purposive sampling. The sample for this research consisted of 33 fourt grades students, namely 13 students at SDN 1 Tamanan and 20 students at SDN 1 Karanganyar. the results of the paired sample t-test showed that H 0 was rejected and H a was accepted so that there were differences before and after the use of audiovisual learning media based on the wordwall game application to increase the literacy of elementary school students with the effectiveness value through the N -Gain test showing an increase, So it can be concluded that audiovisual learning media based on the wordwall game application is able to increase student literacy and is an interesting, fun, valid and practical media to be applied in the learning process in elementary schools.